MANUFACTURING AND CHEMICAL CHARACTERIZATION OF ISABEL RED - Barbosa, Manuella Macêdo; de Sousa, Francisco Wagner; Monteiro, Inês Cristielle da Cunha; Melo, Pedro Augusto Barros; Fernandes, Letícia Castro; Alencar, Emanuelle Priscila Herculano (ARACÊ, 2024)
Considering the potential consumption and economic importance that Isabel wine represents in the Brazilian consumer market, the aim of this research was to study the manufacturing and to determine the chemistry composition of red wine produced from Isabel grapes. The wine fermentation was achieved with 0.2 g/L of Saccharomyces cerevisiae yeast at 25ºC. After seven days of fermentation the correction of sugar was performed. After 40 days, the wine was separated from residues. The wine was clarified with commercial unflavored gelatin at the proportion of 0.2 g/L. The parameters total and volatile acidities, ethanol, dry extract, carotenoids, anthocyanins, total phenolic and reducing sugar were studied. Isabel grapes have the potential to be used to produce wine, hence its economic importance in Brazil. The chemical profile provided essential information about the Isabel red wine and the yeast used for inoculation result in good must fermentation, according to Brazilian legislation.